Configurations of multiple disparities in reading performance: longitudinal observations across France, Germany, Sweden and the United Kingdom - Lenkeit, J; Schwippert, K; Knigge, M (Routledge, 2017)
Research provides evidence that gender, immigrant background and socio-economic characteristics present multiple disadvantaging characteristics that change their relative importance and configurations over time. When evaluating inequalities researchers tend to focus on one particular aspect and often use composite measures when evaluating socio-economic characteristics. Neither can fully represent the complexity of students’ various disadvantaging characteristics, which have autonomous associations with attainment and with each other. This paper investigates how the relative importance and configurations of different disadvantaging factors have changed over time to form educational inequalities and how these changes differ across countries. Data from five PISA cycles (2000–2012) for France, Germany, Sweden and the United Kingdom are used and configurations of gender, immigration background, parents’ occupational and educational levels, and the number of books at home evaluated. Results enable us to relate changes (or lack thereof) in configurations of disadvantaging factors to recent reforms targeted at reducing educational inequality after the first PISA results.